The Involvement of Aβ42 and Tau in Nucleolar and Protein Synthesis Machinery Dysfunction - Maina, Mahmoud B.; Bailey, Laura J.; Doherty, Aidan J.; Serpell, Louise C. (Frontiers in Cellular Neuroscience, 2018)
Alzheimer's disease (AD) is the most common form of dementia and is distinguished from other dementias by observation of extracellular Amyloid-β (Aβ) plaques and intracellular neurofibrillary tangles, comprised of fibrils of Aβ and tau protein, respectively. At early stages, AD is characterised by minimal neurodegeneration, oxidative stress, nucleolar stress, and altered protein synthesis machinery. It is generally believed that Aβ oligomers are the neurotoxic species and their levels in the AD brain correlate with the severity of dementia suggesting that they play a critical role in the pathogenesis of the disease. Here, we show that the incubation of differentiated human neuroblastoma cells (SHSY5Y) with freshly prepared Aβ42 oligomers initially resulted in oxidative stress and subtle nucleolar stress in the absence of DNA damage or cell death. The presence of exogenous Aβ oligomers resulted in altered total tau levels and tau phosphorylation state in the nucleolus revealing an influence of oligomeric Aβ leading to altered distribution of nucleolar tau associated with nucleolar stress. These markers of cellular dysfunction worsen over time alongside a reduction in ribosomal RNA synthesis and processing, a decrease in global level of newly synthesised RNA and reduced protein synthesis. The interplay between Aβ and tau in AD remains intriguing and Aβ toxicity has been linked to tau phosphorylation and changes in localisation. These findings provide evidence for the involvement of Aβ42 and tau in nucleolar and protein synthesis machinery dysfunction in cultured cells. Protein synthesis dysfunction is observed in mild cognitive impairment and early AD in the absence of significant neuronal death.